EFEITO DO FLÚOR E TEMPOS DE ESPERA NA RESISTÊNCIA DE UNIÃO E GRAU DE CONVERSÃO DE UM ADESIVO APLICADO EM ESMALTE CLAREADO - Bittencourt, Bruna Fortes (2012)
The objective of this study was to evaluate the influence of fluoride and time intervals on the bond strength (BS) and degree of conversion (DC) of an adhesive applied on bleached enamel. Sixty human enamel specimens were used, entrenched in PVC tubes and acrylic resin, and submitted to bleaching treatment (n=18): Group HP: HP Maxx (35% hydrogen peroxide); Group HPF: HP Maxx + 1,23% neutral fluoride application; Group PF: Opalescence Boost PF (38% hydrogen peroxide containing 1,1% fluoride). For the restorative procedure, the groups were subdivided into three subgroups (n=6), according to the time interval: immediately, after 7 and 14 days. Tygon tubes were filled with composite resin and positioned on the enamel surface, in order to perform the microshear bond test. DC was observed in Raman spectroscopy. BS (MPa) and DC (%) data were submitted to 2-way ANOVA and Tukey’s post-test, and ANOVA and Dunnet’s post-test (α=0,05). The BS results showed differences between the Group HP in 14 days (21.40±3.45) compared to the groups “immediate” (13.02±4.28) and 7 days (13.67±2.92), the same as verified in Group HPF (14 days: 18.08±2.74, immediate”: 9.74±2.11 and 7 days: 12.66±2.68). For DC, “immediate” Group HP and Group HPF (57.02±7,61 e 66.89±8,57, respectively) differed significantly from 7 and 14 days (HP: 78.15±6.80, HPF: 78.62±8.67 and HP: 77.27±4.60, HPF: 88.09±5.83, espectively). For Group PF, there were no differences between the experimental groups and the control group (p>0.05). It was concluded that fluoride topical application was not effective to reverse low BS and DC values, being necessary wait 14 days to perform the adhesive procedure; but when restorative procedures are required immediately after bleaching, the fluoridated bleaching agent was efficient to maintain BS and DC values.